THE ISSUE OF INSECTICIDE REGULATION ON SKIN SURFACE FOR PREDICTING THE RISK OF OCCUPATIONAL SKIN PATHOLOGY IN AGRICULTURAL WORKERS - Heorhii P. Bardov; Mykola V. Kondratiuk; Olena P. Vavrinevych; Oleksandr S. Vavrinevych (Клінічна та профілактична медицина)
Aim. To establish insecticide surface skin exposure standards and predict the risk of occupational skin pathology in agricultural workers to develop preventive measures against diseases caused by dermal pesticide exposure.